PENGARUH RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2011-2018 - Hari Dwi Anggraini; Miftahuddin Miftahuddin; Ahmad Prayudi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE) Against Stock Prices in Manufacturing Companies Listed on the IDX. This type of research is causal comparative research that is conducted to compare a variable (research object), between different subjects or different times and find a causal relationship. The population in this study are all financial statements of PT. Gudang Garam Tbk. The sample used is the financial statements at PT. Gudang Garam Tbk from 2011-2018. Based on the results of the t test ROA has a significance value of 0.035 0.05 and has a regression coefficient of (2.57058) which means that ROA has a significant influence on stock prices at PT. Gudang Garam Tbk. ROE has a significance value of 0.473 0.05 and has a regression coefficient of (-776) which means that partially ROE has no influence on stock prices at PT. Gudang Garam Tbk. Based on the results of the F test, ROA, ROE has a level of significance value at the output of 0.022 0.05 and shows the value of Fcount Ftable where (9.020) (5.14) which means the effect of ROA and ROE on stock prices simultaneously (together ). The value of the Determinant Coefficient (R2) is 0.783. So it can be concluded that by 78.3%. Stock price is influenced by ROA, ROE and the remaining 21.7% is influenced by other variables not examined in this study.